Practising planners’ perceptions of post-1994 planning law and settlement planning and development processes: A Western Cape case study - Harris, Marshallene; Oranje, Mark (Town and Regional Planning, 2024)
While a significant body of academic work has been compiled on the transformation of planning law since the end of apartheid, far less has been produced on the perceptions of practising planners of these new laws, and their impacts on the planning profession’s stated objective of contributing to the creation of quality human settlements. This article seeks to assist in filling this gap in the field by reporting on a study into the perceptions of practising planners in the Western Cape in this regard. The study involves research into the views of professional planners on planning laws applied during and post-apartheid and the impact of these laws on human settlement planning and development. Data was collected through semi-structured interviews with 25 professional planners employed in the public and private sectors. The data sample, limited to the Western Cape province, was regarded as a starting point for further research on the perception of planners in these regards in the remaining eight provinces in the country. The key findings of this study are that planners by and large welcome the new planning legislation and view it as an improvement on the old. The challenges being experienced are mainly related to the institutional and financial landscape in which the law plays out rather than the law itself, notably lengthy planning processes; a focus on meeting housing-delivery targets at the cost of other equally important settlement development objectives; capacity, and budget constraints.